Information Technology Risk Management Analysis on Money Transfer Services in Post Offices Using Framework Standardization ISO 22301 - Michael Raynard; Gunawan Wang (Departement of Mathematics Education, 2022)
State-Owned Enterprises (BUMN) have realized the importance of information technology, one of which is PT. POS (PERSERO) Indonesia. The purpose of this study is to analyze the management of Information Technology that is currently running at PT. POS (Persero) Indonesia lhokseumawe branch, to find out the Capability Level. The Post Office is an organization engaged in the delivery of goods. The organization has used information technology to support business activities. Money transfer is an application that is used to record every shipment of goods made by consumers starting from the data of the sender of the goods, the data of the goods, and the data of the recipient of the goods. However, it is undeniable that every risk that occurs can interfere with the performance of the money transfer application. Therefore, it is necessary to analyze the risk of the information technology used. In this study, researchers tried to implement the ISO 22301 risk management framework to see every possible risk contained in the money transfer application. The final result of this research is expected to help organizations in seeing and knowing what actions must be taken against any possible risks or threats that occur around the money transfer application based on the level of risk